Does electoral observation influence electoral results? - Leeffers, Stefan (2022)
Electoral fraud is a common problem in young democracies. Election observers constitute one possible remedy. Yet, quantitative evidence of the causal effects of different types of observers is scarce. Data on the random assignment of observers during Mozambique's 2009 general elections are used to estimate the impact that observers have on electoral results. We are able to distinguish between domestic observers that stayed in the same ballot table for the whole of the election day, who were deployed countrywide, and international observers that circulated across a number of ballot locations, assigned within selected districts. We show that the presence of domestic observers reduced voter turnout and increased the share of blank votes countrywide. This suggests a reduction of ballot fraud activities. For the selected districts in which international observers were active findings are less clear, as we do not find ballot fraud-reducing effects for any of the two types of observers. A possible interpretation is that local politicians anticipate the presence of international electoral observers in convenient districts or use different fraudulent strategies.